Cascadic Multigrid for Finite Volume Methods for Elliptic Problems (Journal of Computational Mathematics, 2021)
In this paper, some effective cascadic multigrid methods are proposed for solving the large scale symmetric or nonsymmetric algebraic systems arising from the finite volume methods for second order elliptic problems. It is shown that these algorithms are optimal in both accuracy and computational complexity. Numerical experiments are reported to support our theory.
Keywords: Cascadic multigrid; Finite volume methods; Elliptic problems.